2005
DOI: 10.1097/01213011-200506000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Association of catechol-O-methyltransferase with smoking cessation in two independent studies of women

Abstract: This first report of a significant association between COMT Val108/158Met and smoking cessation suggests that COMT variation has an effect on smoking behavior in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 28 publications
3
72
3
Order By: Relevance
“…For example, plasma concentrations of varenicline could be measured in individuals prescribed this medication 34 to test for the effect of functional OCT2 alleles on medication plasma levels, to test association between medication plasma levels and prospective abstinence, and on the influence of the functional OCT2 alleles on prospective abstinence, as has been reported for the bupropion metabolite hydoxybupropion and CYP2B6 variation. 81 Effects of the functional OCT2 allele on brain structure and function may be observable, given prior studies that have identified effects on brain structure 82 and function 83 of cholinergic 47,84 and dopaminergic 40,85 alleles that influence smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, plasma concentrations of varenicline could be measured in individuals prescribed this medication 34 to test for the effect of functional OCT2 alleles on medication plasma levels, to test association between medication plasma levels and prospective abstinence, and on the influence of the functional OCT2 alleles on prospective abstinence, as has been reported for the bupropion metabolite hydoxybupropion and CYP2B6 variation. 81 Effects of the functional OCT2 allele on brain structure and function may be observable, given prior studies that have identified effects on brain structure 82 and function 83 of cholinergic 47,84 and dopaminergic 40,85 alleles that influence smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…[108][109][110] The low activity Met allele appears to be protective against current smoking; Caucasian women with two Met alleles were more likely to be ex-smokers and had higher abstinence rates when randomized to either nicotine spray or transdermal patch in an open-labeled trial. 111 Further, several gender-and ethnic-specific haplotypes containing the Met allele have a protective effect against ND. 112 However, other studies have failed to find any association between the Val108/158Met variant and smoking initiation, cessation or cigarette consumption.…”
Section: Mk Ho and Rf Tyndalementioning
confidence: 99%
“…Our results are consistent with previous reports of no association between COMT and smoking initiation (David et al 2002, Guo et al 2007) and persistent smoking (David et al 2002, Guo et al 2007). However, one study found the G allele to be associated with persistent smoking among women (Colilla et al 2005), and another found it to be associated with current smoking status (Enoch et al 2006). The associations between COMT and other smoking outcomes have been examined with mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Higher DBH plasma concentrations may influence drug dependence (Cubells et al 2000, Gabel et al 1995. However, so far the evidence concerning variants in the COMT, DBH and MAO-A genes in relation to smoking behaviors has been inconsistent (Beuten et al 2006, Colilla et al 2005, David et al 2002, Enoch et al 2006, Guo et al 2007, Han et al 2008, Jin et al 2005, Johnstone et al 2004, McKinney et al 2000, Munafo et al 2008, Tochigi et al 2007, Ton et al 2007). …”
Section: Catechol-o-methlyltransferase (Comt) Dopamine Beta-hydroxylmentioning
confidence: 99%